Non-invasively Measured Venous Oxygen Saturation as Early Marker of Impaired Oxygen Delivery in Preterm Neonates - Mileder, Lukas P.; Buchmayer, Julia; Baik-Schneditz, Nariae; Schwaberger, Bernhard; Höller, Nina; Andersen, Chad C.; Stark, Michael J.; Pichler, Gerhard; Urlesberger, Berndt (Frontiers in Pediatrics, 2022)
Introduction Adequate oxygen supply for preterm neonates may be defined through non-invasive measurement of venous oxygen saturation (SvO2) and fractional oxygen extraction using near-infrared spectroscopy (NIRS). We investigated whether there was a difference in peripheral muscle SvO2 (pSvO2) and peripheral fractional oxygen extraction (pFOE) in preterm neonates with early inflammation/infection compared to healthy subjects during the first 72 h after birth. Materials and Methods We retrospectively analyzed secondary outcome parameters of prospective observational studies, including preterm neonates at risk of infection in whom peripheral NIRS measurements were performed in combination with venous occlusions. Early neonatal inflammation/infection was diagnosed by clinical signs and laboratory parameters. Peripheral muscle tissue oxygenation index (pTOI) was measured using either NIRO 300 or NIRO 200-NX (both Hamamatsu Photonics, Japan) on the patients' lower legs. Using 20-s venous occlusions, pSvO2 and pFOE were calculated incorporating simultaneous measurements of arterial oxygen saturation (SpO2). Results We analyzed measurements from 226 preterm neonates (median gestational age 33.9 weeks), 64 (28.3%) of whom were diagnosed with early neonatal inflammation/infection. During the first 24 h after birth, pSvO2 (66.9% [62.6–69.2] vs. 69.4% [64.6–72.0]; p = 0.04) and pTOI (68.6% [65.3–71.9] vs. 71.7% [67.3–75.1]; p = 0.02) were lower in those neonates with inflammation/infection, while there was no such difference for measurements between 24–48 and 48–72 h. Discussion NIRS measurement of pSvO2 and pFOE is feasible and may be utilized for early detection of impaired peripheral oxygen delivery. As pTOI was also significantly lower, this parameter may serve as substitute for diminished regional oxygen supply.